What will Europe 1992 mean for the Caribbean? - Stevens, Christopher (Overseas Development Institute LondonGB)
Paper sets 'Europe 1992' within the context of Euro-South relations over the past two decades and the trade options open to the Caribbean. Reviews the banana issue, the problems for sugar and the case of Jamaica with regard to duty-free access to the European market. Concludes that the Caribbean has more to lose potentially from '1992' than any other region of the South because the internal liberalisation of the Single European Market threatens exports that depend on managed markets. Suggests that the main constraint on the Caribbean benefitting from the positive trade creating side of 1992 is its failure to diversity. Maintains that the effective provisions of the Banana protocol must be preserved at all costs.